JIRA 6.x administration cookbook : over 100 hands-on recipes to help you efficiently administer, customize, and extend your JIRA 6 implementation /: over 100 hands-on recipes to help you efficiently administer, customize, and extend your JIRA 6 implementation. (2014) - Li, Patrick
No abstract available